PENGARUH KUALITAS PRODUK KOPI TERHADAP KEPUTUSAN PEMBELI DI POINT COFFEE PEDURENAN - Dwi Lolla Octavyan; Sofiani Sofiani (Kepariwisataan: Jurnal Ilmiah, 2021)
Indonesia as one of the largest coffee producing countries in the world has an important role in global trade, namely the specialty coffee trade. Specialty coffee is one of the leading commodities for coffee producing countries like Indonesia because of the taste of the coffee. The quality of the product itself has an understanding that the product offered by the seller has more selling value that must be owned by competitors' products, therefore the company is trying to focus on the quality of the product and compare it with the products offered by competing companies. This research is associative research using a quantitative approach. With the aim to analyze the effect of Coffee Beverage Product Quality on Buyer's Decisions at Point Coffee Pedurenan, South Jakarta, as well as find out which factors have a dominant influence on Buyer's Decisions at the Coffee Shop. The sample in this study amounted to 100 respondents who had visited Point Coffee by using the Probability Sampling method with the Simple Random Sampling technique. The data was collected using questtionnaires and distribute it directly to buyers at Point Coffee. The suggestion from this research is that the owner of Point Coffee can maintain the hygiene that has been applied by the workers, Increase again the Quality, Quantity, Variation, and Innovation of coffee beverage products in terms of flavor, to meet the buyer's decision. And Point Coffee is more innovative so that buyers don't get bored easily if they come again at Point Coffee.Keywords: Product Quality, Service Quality, Purchasing Decisions